Visualising Chinese presence: an analysis of the contemporary arts of Zambia and Zimbabwe - Zhang, Lifang (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
With the revival and rapid growth of relations between China and African countries in the present century, the "China-Africa relationship" has become a topic of close attention globally and the media and politicians have been dominating the mainstream discourses with dichotomised narratives. China-Africa engagement has also spurred academic research, most of which is oriented toward large-scale economic, political, and strategic concerns. In this context, it is significant to conduct in-depth research exploring specific engagement between Chinese and African people on the ground. Contemporary artists based in Africa have started to represent, through artworks and performances, their experiences and expressions of relations between China and various African countries. However, an examination of twenty-first century connections between Africa and China in relation to the contemporary visual arts is a new area of study and only a limited number of scholarly works exist. To contribute to the research in this area, this thesis explores the ways in which artists engage with specific realities and lived-experiences of Chinese presence through their artistic practices, with a focus on a selection of artists from Zambia and Zimbabwe. Through visual analysis, interviews and field work, this thesis provides a systematic investigation of contemporary arts of Zambia and Zimbabwe in relation to Africa- China encounters, engaging with four aspects: the discursive field, the material presence, individual experiences of encounters, and the broader relational connections within the arts. This thesis argues that, motivated by the histories and realities of African societies, artists from Zambia and Zimbabwe, through their artistic practices, form part of the Africa-China engagement and insert their agencies in the south-south relations between Africans and Chinese. Therefore, this thesis demonstrates the value in approaching the broader discussion on Africa-China engagements from the perspective of contemporary art, arguing that, with the social concerns of the artists and the expressive capacity of creative forms, visual arts are able to embrace diversity, dynamics, complexities and contradictions, and, therefore, can develop the topic beyond the stereotypical narratives about Africa-China relations to a more nuanced understanding of African-Chinese encounters in specific contexts.
Keywords: Art, Modern -- 21st century; Art, Modern -- 21st century -- Chinese influences; China -- Relations -- Zambia; China -- Relations -- Zimbabwe; Art and society -- Zambia; Social practice (Art) -- Zambia; Art and globalization -- Zambia; Art and society -- Zimbabwe; Social practice (Art) -- Zimbabwe; Art and globalization -- Zimbabwe